FORMULATION AND EVALUATION OF ASPIRIN-LOADED PLGA NANOPARTICLES FOR OPHTHALMIC USE - PETHE, ANIL; SHANBHAG, ARYA; SHERJE, ATUL; AGRAWAL, SURENDRA (International Journal of Applied Pharmaceutics, 2023)
Objective: The objective of this work was to increase the bioavailability of Aspirin to the retina by increasing its bioavailability to blood. This was achieved by forming aspirin-loaded PLGA nanoparticles Methods: Aspirin-loaded PLGA nanoparticles were prepared by a solvent evaporation process. The PLGA was dissolved in the proper solvent and added dropwise to the Aspirin-albumin solution revolving at 3000 rpm. Glutaraldehyde was used as a cross-linker at 20% concentration. The nanoparticles were obtained after passing the solution through HPH and subsequent centrifugation. Results: The prepared nanoparticles were found to be spherical with the smooth surface as seen in SEM. and with a size of 160.9 nm. Aspirin-loaded PLGA nanoparticles showed in vitro drug release of 71.4 % and ex-vivo permeation of 66.2 %. The formulation was found to be stable for six months. Conclusion: The developed aspirin-loaded polymeric nanoparticles could be effective for the controlled delivery of aspirin in the early prevention of diabetic retinopathy.